Evolution of intensity noise and hybrid correlation. (28th April 2017) - Ahmed, Irfan; Lau, Condon; Wang, Ruimin; Zhang, Da; Li, Xinghua; Li, Kangkang; Li, Changbiao; Zhang, Yanpeng
Abstract: We report the evolution of spontaneous parametric four-wave mixing (SP-FWM) as a small peak in the dip of Autler–Townes splitting in the medium of coherent non linear crystal of Pr 3+ :Y2 SiO5 . We demonstrate the results of a composite signal with evolution from pure fluorescence to a hybrid state of light to pure SP-FWM. By investigating the composite signal in frequency/time domains and studying hybrid correlations (positive/negative or anti-correlation) among three channels, i.e. Stokes (anti-Stokes) with composite signal, we demonstrate the evolution of SP-FWM processes from fluorescence. Such correlations can have potential applications in all-optical communication and quantum teleportation.